2015
DOI: 10.1371/journal.pone.0131945
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Inter-Fractional Fiducial Migration during Image-Guided Lung Stereotactic Body Radiotherapy Using SuperLock Nitinol Coil Fiducial Markers

Abstract: ObjectivesStereotactic body radiotherapy (SBRT) is being increasingly used for the treatment of patients with lung cancer or lung metastasis who are medically unfit to undergo resection. In order to improve accuracy and confidence in targeting tumors, many centers rely on fiducial implantation. We evaluated the migration of a novel fiducial marker specifically designed for lung tissue implanted via electromagnetic navigation bronchoscopy (ENB).MethodsWe retrospectively quantified the individual and group migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The authors also observed minimal interfractional fiducial migration during the course of radiation treatment. 27 In another study, the VortX coil FM had a retention rate of 96.7% (from pretreatment radiation planning CT scan to the first day of therapy) compared to two-band (72%) and the gold-seed (69%) markers. 19 The VortX FM was the second most common marker utilized in the NAVIGATE study.…”
Section: Discussionmentioning
confidence: 96%
“…The authors also observed minimal interfractional fiducial migration during the course of radiation treatment. 27 In another study, the VortX coil FM had a retention rate of 96.7% (from pretreatment radiation planning CT scan to the first day of therapy) compared to two-band (72%) and the gold-seed (69%) markers. 19 The VortX FM was the second most common marker utilized in the NAVIGATE study.…”
Section: Discussionmentioning
confidence: 96%
“…Oldrini et al [ 21 ] evaluated the imaging technique for fiducial placement and concluded that ultrasound-guided placement is equivalent to CT guided placement. Rong et al [ 24 ] evaluated the migration parameters after placement. Choi et al [ 25 ] evaluated the safety and technical feasibility of endoscopic ultrasonography (EUS)-guided fiducial placement.…”
Section: Discussionmentioning
confidence: 99%
“…The place to insert (within or around the tumor), and the number of fiducial markers (1 to 3 or more) to insert is not well established. The migration rate of some markers is very low (21).…”
Section: To Help Stereotactic Radiosurgerymentioning
confidence: 97%